2020
DOI: 10.1186/s12916-020-01601-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the contribution of different age strata to vaccine serotype pneumococcal transmission in the pre vaccine era: a modelling study

Abstract: Background Herd protection through interruption of transmission has contributed greatly to the impact of pneumococcal conjugate vaccines (PCVs) and may enable the use of cost-saving reduced dose schedules. To aid PCV age targeting to achieve herd protection, we estimated which population age groups contribute most to vaccine serotype (VT) pneumococcal transmission. Methods We used transmission dynamic models to mirror pre-PCV epidemiology in Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Similar to their key role in pneumococcal transmission generally [22,[26][27][28], we find that 2-6 year old children are the likely main transmitters of pneumococcal infection to infants. This has important implications for the optimal design of pneumococcal vaccination strategies, particularly those that aim to sustain herd protection while reducing direct protection in infancy [10]: while the exact duration of protection from pneumococcal conjugate vaccines remains relatively uncertain [29], booster dose schedules may induce longer lasting protection and hence may be preferred in settings with high carriage prevalence in older children and hence a potentially high contribution to the pneumococcal infection pressure from that age group [30].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar to their key role in pneumococcal transmission generally [22,[26][27][28], we find that 2-6 year old children are the likely main transmitters of pneumococcal infection to infants. This has important implications for the optimal design of pneumococcal vaccination strategies, particularly those that aim to sustain herd protection while reducing direct protection in infancy [10]: while the exact duration of protection from pneumococcal conjugate vaccines remains relatively uncertain [29], booster dose schedules may induce longer lasting protection and hence may be preferred in settings with high carriage prevalence in older children and hence a potentially high contribution to the pneumococcal infection pressure from that age group [30].…”
Section: Discussionsupporting
confidence: 62%
“…We have previously shown that pneumococcal infection risk is correlated with the frequency of physical contacts [5,6]. Here we expand that notion by including the probability that contacts are infected with pneumococci, similar to how age stratified dynamic mathematical models are constructed [3,22,23], and thus provide direct evidence for the value of social contact structure as a proxy for disease transmission routes in mathematical models. Furthermore, we suggest that the combination of social contacts and age dependent infection probabilities provides a simple and useful method to identify likely transmission routes, without the need for more complex mathematical modelling or the need for longitudinal data collection [24,25].…”
Section: Discussionmentioning
confidence: 53%
“…The first age group to rebound to the pre-pandemic baseline was 0-to 4-year-olds, possibly reflecting this group's role in population-wide transmission of pneumococci. (22,23) Despite a sharp drop in the number of cases in 2020 and the first quarter of 2021, the proportion of vaccine serotypes remained consistent, both overall and stratified by age group and by geographic regional group. The southernmost regional group, consisting of two large federal states, exceeded baseline IPD cases in July, as did four additional federal states.…”
Section: Discussionmentioning
confidence: 97%
“…However, herd immunity is the result of a complex interplay of factors including bacterial physiology, booster dose coverage, the average age of pneumococcal carriage, duration of vaccine protection against the carriage, and social mixing patterns [ 88–90 ]. Additionally, the high average age of carriage, intense social mixing, and the waning of PCV protection against carriage (estimated half-life is 4–6 years) may imply that, in some settings, older children are a key source of pneumococcal transmission and are not fully protected in a 2p+1 schedule [ 91 , 92 ]. A school entry PCV booster dose may be necessary to interrupt transmission and increase herd protection [ 91 ].…”
Section: Optimal Vaccination Strategiesmentioning
confidence: 99%